An Empirical Analysis of Turkey’s Foreign Trade Trends: 2015 – 2024 - Esmer Aliyeva (Challenges and Issues of Modern Science)
Purpose. This article analyzes the trade balance of the Republic of Türkiye for 2015–2024, examining import–export dynamics over a ten-year interval and identifying the main drivers of the persistent deficit. Design / Methodology / Approach. The study draws on data from Trade Map, international trade statistics for business development, TURKSTAT, and open-data releases from other organizations; annual trade values and year-over-year growth rates were compared using descriptive statistics and time-series comparisons to assess trends and bilateral flows. Findings. Throughout the period, import values consistently exceeded export values, generating a sustained trade deficit. Although exports grew steadily, the faster rate of import growth resulted in a widening gap, indicating that Türkiye purchased more goods and services abroad than it sold. Theoretical Implications. The results underscore the value of empirical statistical analysis for understanding structural trade imbalances and support refinement of theoretical models addressing trade deficits in emerging economies. Practical Implications. Strategic imports—particularly energy products and industrial raw materials—have driven the deficit, with substantial volumes sourced from Russia and China; these insights can inform targeted import-substitution policies and measures to strengthen domestic production. Originality / Value. The research synthesizes multiple data sources to present updated empirical insights into Türkiye’s principal export markets (Germany, the USA, the UK) and largest import partners (China, Russia), and highlights diversification toward Asian and Caucasus nations over the study period. Research Limitations / Future Research. Future research should employ mathematical modeling techniques to test causality and explore counterfactual policy scenarios. Paper Type. Applied, Empirical article.